Hurricanes, Economic Growth and Transmission Channels - Empirical Evidence for Developed and Underdeveloped Countries - Michael Berlemann; Daniela Wenzel (Center for Economic Studies and ifo Institute (CESifo), 2016)
While the short-term growth consequences of natural disasters are comparatively well studied, there is little knowledge how disasters affect long-run growth. Based on truly exogenous storm indicators, derived from a meteorological database, we show that the growth effects of tropical storms go well beyond the short-term perspective. These negative growth effects of hurricanes are especially pronounced in underdeveloped countries which have comparatively little possibilities to protect against storm consequences. We show that the negative growth effects in underdeveloped countries are amplified by an increase in net fertility and a decrease in educational efforts in the aftermath of occurring hurricanes.
Keywords: Q54; 330; economic growth; natural disasters; tropical storms; transmission channels